Wind Power in the German System - Research and Development for the Transition towards a Sustainable Energy Future - Luther, Matthias; Rohrig, Kurt; Winter, Wilhelm (Wind Energy Engineering, 2017)
As a result of developments within the last 30 years, wind energy has become a fundamental pillar for the electrical energy supply in Germany. As of today and beside other renewable energy sources, wind power generation is at the center of the ongoing transition process of the German energy system. The chapter describes the state of play as well as future challenges with respect to large-scale wind energy integration into the German and European power system. Based on existing facts and figures and a long-term outlook, the developments in the onshore and offshore wind power technology together with the necessary grid development plans and relevant network codes are provided. Recent experiences with respect to wind integration in Germany call for complex interoperability analyses between transmission and distribution including the sector coupling of generation and storage plants. Furthermore, ongoing research activities concerning new intersystem phenomena are addressed.
Keywords: Wind power integration; turbine technology; network operation; grid development; GDP; O-GDP; TYNDP; network codes; forecast systems; wind cluster management